POWER AND ADVICE TO DETACHMENT: THE WOMEN’S LANGUAGE AND MEANING IN THEWIZARDLIZ YOUTUBE VIDEO - I Gst Ayu P. Jesika Sita Devi; Putu Ayu Trisna Febrianty; Nyoman Dewi Pitaloka Cahyadi (Esteem Journal of English Education Study Programme, 2025)
This research aims to identify the women's language features present in the utterances of the content creator behind the YouTube channel TheWizardliz, as well as to interpret the conceptual meanings conveyed through those utterances. Utilizing qualitative research methods, the study applies two key theoretical frameworks: Lakoff’s (2004) theory on women’s language features and Leech’s (1981) theory of meaning. The analysis reveals the deliberate use of various women’s language features—such as one lexical hedge, three tag questions, three instances of rising intonation in declarative sentences, one empty adjective, two intensifiers, and five occurrences of hypercorrect grammar. These linguistic choices serve specific functions, including softening statements, seeking validation, emphasizing important ideas, and ensuring grammatical precision. Furthermore, the study explores the underlying conceptual meanings, suggesting that these language features are used to empower women and encourage them to break free from toxic relationships.